Effects and Perceptions of Mobile Learning in Higher Education - Sami Al-Qatawneh; Najeh Alsalhi; Mohd. Eltahir; Fayiz Althunibat; Mazan Jaradat; Khaled Aljarrah (Emerging Science Journal, 2022)
Objectives: This study aimed to investigate the effect of mobile learning on students’ achievement in the grammar of the Arabic language, and their attitude towards the use of mobile learning. Methods/Analysis: The study was conducted using a quasi-experimental design, case study. The sample comprised 170 students, divided into two groups: an experimental group (n = 87) and a control group (n = 83). An achievement test and a questionnaire were used to collect data, which was analyzed using SPSS. Findings: The findings revealed statistically significant differences between the two groups, with the experimental group showing better scholastic achievement on the test. The results also show that the students of the experimental group were more positive towards mobile learning. Novel contribution: The study recommends further studies on the use of mobile learning in universities and schools. It is necessary to emphasize and focus on further studies on the use of mobile learning within universities and schools to confirm and provide evidence of the significance of mobile learning in terms of facilitating, promoting, and enhancing the educational process. Doi: 10.28991/ESJ-2022-SIED-06 Full Text: PDF